Pelayanan Musik sebagai Mediasi Afektif dalam Pembentukan Iman Jemaat: Studi Empiris pada Gereja Kristen Indonesia Palu - Baginda, Leopold M.; Umbur, Recky M. (JURNAL ILUMINASI, 2026)
This study examines the role of worship music in the formation of congregational faith within a contemporary church context. While previous studies often emphasize the aesthetic and participatory aspects of music, this article argues that worship music functions as a form of affective mediation that facilitates faith experience rather than directly producing faith formation. Using a quantitative correlational design, data were collected from 191 respondents at Gereja Kristen Indonesia (GKI) Palu. The analysis shows a moderate and significant relationship between music ministry and faith formation (r = 0.552; p < 0.05). The findings indicate that worship music contributes primarily through the affective dimension by enhancing spiritual engagement and experiential participation in worship. However, its role remains complementary and must be integrated with theological teaching and pastoral formation. This study contributes to practical theology by proposing a relational model in which music operates within a broader ecosystem of faith formation rather than as an isolated factor.